Impairment of pulmonary-artery endothelium-dependent relaxation in chronic obstructive lung disease is not due to dysfunction of endothelial cell membrane receptors nor to L-arginine deficiency. - Dinh-Xuan, A. T. (Nature Publishing Group, 1993)
1. Endothelium-dependent relaxation mediated by endothelium-derived relaxing factor (EDRF) or nitric oxide (NO), is impaired in pulmonary arteries (PA) of hypoxic patients with chronic obstructive lung disease (COLD). To determine the mechanisms responsible for this impairment, we compared the response of rings of isolated PA from 12 COLD patients and 8 controls to the endothelium-dependent vasodilators acetylcholine (ACh), adenosine diphosphate (ADP), and the calcium ionophore, A23187. The response of PA rings to the endothelium-independent nitro-vasodilator sodium nitroprusside (SNP) was also studied in both groups. The PA rings had been pre-contracted by the alpha-adrenoceptor agonist phenylephrine (PE). 2. Endothelium-dependent relaxation was significantly reduced in PA rings from COLD patients as compared with controls when tested with ACh (37.8 +/- 8.8% vs 73.4 +/- 7.9%), ADP (38.4 +/- 6.7% vs 80 +/- 5.6%), and the calcium ionophore, A23187 (35.8 +/- 6.1% vs 87 +/- 6.6%). Relaxation with SNP was, however, significantly greater in PA rings from COLD patients (99.4 +/- 0.6% vs 90.3 +/- 3.1%), as was the contractile response to PE (1.91 +/- 0.21 g vs 1.33 +/- 0.15 g). Pretreatment with the specific inhibitor of NO formation, NG-monomethyl-L-arginine (L-NMMA; 10(-4) M) significantly reduced the relaxation to ACh in all PA rings. This inhibition could be reversed by L-arginine (10(-3) M), the substrate for NO synthesis. Pretreatment with L-arginine alone, however, did not restore the impaired endothelium-dependent relaxation of PA rings from COLD patients.(ABSTRACT TRUNCATED AT 250 WORDS)